Gay-Related Rejection Sensitivity as a Risk Factor for Condomless Sex. - Wang, Katie; Pachankis, John E (AIDS and behavior, 2015)
Gay-related rejection sensitivity has been linked to numerous adverse health outcomes, but its relationship to condomless sex remains unexamined. The present study investigated the role of gay-related rejection sensitivity as a predictor of condomless sex. Gay and bisexual men completed questionnaires measuring rejection sensitivity and condom use self-efficacy as well as a timeline followback interview regarding past 90-day sexual behaviors. Gay-related rejection sensitivity was positively associated with the number of condomless anal sex acts with casual partners, and condom use self-efficacy mediated this association. These findings have important implications for effective HIV prevention efforts among this at-risk population.